Lost in Evaluation: The Intricacies of First‐ and Second‐Order Evaluations in Auditors' Promotion Committees in the Big 4 Audit Firms - Garnier, Claire; Stenger, Sébastien; Roulet, Thomas (Contemporary Accounting Research, 2026)
ABSTRACT The evaluation of auditors in the Big 4 audit firms has largely remained a “black box” in accounting and audit research. Little is known about how these processes operate within audit firms or how they relate to promotion decisions. This study addresses this gap by providing direct insight into promotion committee decision‐making. Drawing on the sociology of evaluation, we develop an analytical model to map this process, highlighting the role of collective deliberation, the interplay between first‐ and second‐order evaluations, and the feedback effects of evaluation. Empirically, we rely on a unique multi‐method qualitative data set that focuses on the micro‐level dynamics of auditor evaluation and promotion. Our data includes non‐participant observation of two promotion committees in the Paris office of a Big 4 firm, complemented by 61 interviews. The findings show that auditors' evaluations are not solely based on pre‐assessments made by their direct supervisors but emerge through collective negotiation. This negotiation produces second‐order judgments that determine the auditors' final rankings. In these deliberations, the supervisor's voice and the political dynamics among supervisors carry significant weight. We conclude that the evaluation process hinges less on auditors' intrinsic professional qualities than on how managers' evaluative judgments are themselves assessed. These findings generate both empirical and theoretical contributions to the literature on auditing as a profession and on social evaluation.